Indonesia’s Diplomacy on Flight Safety Issues - Dinar Dewi Kania; Ariesa Ulfa; Mustika Sari (Institut Transportasi dan Logistik Trisakti, 2020)
This paper aims to explain the development of aviation safety in Indonesia prior to the removal of the ban on flights of Indonesian Airlines by the European Commission during the 2007-2018 period, and to examine the diplomatic steps taken by the Indonesian government concerning the removal of the ban. This article employs a qualitative approach which is a literature study. Data were obtained from various official documents and reports, as well as articles and news related to the issue of Indonesian airline's flight ban by the European Commission. The results exhibit a lengthy diplomacy process that took place in the year 2007-2018, illustrating the weakness in the aviation safety aspect of Indonesia's aviation that must be improved. The Indonesian government must continue to strive for the independence of the country's national aviation sector so that it is able to take a prominent role internationally and not to heavily depend on the global transportation business. Economic integration in the aviation sector with all ASEAN countries must also be strengthened to balance the strength of the aviation industry in the European countries and the United States, especially following the horizontal agreement. With such integration in the aviation sector, it is hoped that Indonesia will be able to focus on regional market forces.